2021
DOI: 10.1093/ve/veab002
|View full text |Cite
|
Sign up to set email alerts
|

Designing transmissible viral vaccines for evolutionary robustness and maximum efficiency

Abstract: The danger posed by emerging infectious diseases necessitates the development of new tools that can mitigate the risk of animal pathogens spilling over into the human population. One promising approach is the development of recombinant viral vaccines that are transmissible, and thus capable of self-dissemination through hard to reach populations of wild animals. Indeed, mathematical models demonstrate that transmissible vaccines can greatly reduce the effort required to control the spread of zoonotic pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Unintentional spread of vaccine viruses from vaccinated to unvaccinated individuals can complicate the use of transmissible live attenuated vaccines (LAVs). 1 , 2 , 3 , 4 While self-dissemination is desirable in some scenarios, specifically when herd immunity is sought in wildlife, 5 uncontrolled circulation of vaccine viruses potentially increases the risk of reversion to virulence. 2 , 3 , 4 Recombination between different vaccine viruses or vaccine and field viruses is particularly problematic because it can give rise to recombinants with increased virulence, transmissibility, or immune evasion capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Unintentional spread of vaccine viruses from vaccinated to unvaccinated individuals can complicate the use of transmissible live attenuated vaccines (LAVs). 1 , 2 , 3 , 4 While self-dissemination is desirable in some scenarios, specifically when herd immunity is sought in wildlife, 5 uncontrolled circulation of vaccine viruses potentially increases the risk of reversion to virulence. 2 , 3 , 4 Recombination between different vaccine viruses or vaccine and field viruses is particularly problematic because it can give rise to recombinants with increased virulence, transmissibility, or immune evasion capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…A remaining uncertainty, however, is that natural selection is expected to purge antigenic inserts from viral vectors. Although techniques to reduce the loss of inserts are advancing [ 27 ], this phenomenon has potential to create competition between circulating vaccine strains and “ex-vaccine” strains that have reverted to wild type and may have a fitness advantage over remaining vaccine strains [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, other studies have suggested superinfection is much more challenging ( 30 32 ) and may be achievable only by genetically differentiated MCMV strains. If superinfection requires genetic divergence, transmissible vaccines constructed from locally common betaherpesvirus strains or constructed in a way that results in the rapid loss of their immunogenic cargo are unlikely to succeed ( 15 , 16 , 33 ). Second, our inferences drawn from wild populations assume the geographic distribution of MCMV prevalence represents an equilibrium state and that differences in equilibrium prevalence thus reflect location specific transmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous modeling efforts have demonstrated the potential benefits of vaccine transmission ( 9 , 13 17 ), these models have been general and not parameterized for specific candidate vaccine vectors or zoonotic pathogens. Further, existing models have focused almost exclusively on steady-state solutions and have not addressed the timescale over which zoonotic pathogens can be eliminated.…”
mentioning
confidence: 99%